Optimalisasi Strategi Komunikasi Digital BPKH dalam Meningkatkan Transparansi dan Partisipasi Generasi Muda pada Tata Kelola dana Haji di Indonesia - Elistiana Elistiana; Elsa Mayori (UIN AM. Sangadji Ambon, 2026)
This study examines the optimization of digital communication strategies implemented by Badan Pengelola Keuangan Haji (BPKH) in enhancing transparency and youth participation in the governance of Hajj funds in Indonesia from an Islamic economics perspective. Using a qualitative approach with thematic analysis, the study analyzes official BPKH publications, including annual reports, financial statements, and digital communication channels. The findings indicate that although BPKH has demonstrated strong financial transparency and accountability in compliance with Sharia governance principles, its communication practices remain predominantly one-way, formal, and report-oriented. Such an approach is not aligned with the digital consumption patterns of Generation Z and Millennials, resulting in information asymmetry and limited public engagement. This condition potentially weakens the realization of the principles of amanah (trust) and kashf al-ḥāl (transparency) in the management of Islamic public funds. The study concludes that adopting an interactive, youth-oriented digital communication model is not merely a technical innovation but a strategic necessity to strengthen public trust, encourage meaningful participation, and ensure the sustainability of Hajj fund governance. Practical implications include platform-specific communication strategies, narrative framing based on Islamic values, and collaborative engagement with young Muslim content creators.